Intracranial Arterial Calcification and Intracranial Atherosclerosis: Close but Different - Du, Heng; Li, Jia; Yang, Wenjie; Bos, Daniel; Zheng, Lu; Wong, Lawrence Ka Sing; Leung, Thomas W.; Chen, Xiangyan (Frontiers in Neurology, 2022)
Background and purpose Intracranial arterial calcification (IAC) may be present in the intimal or medial arterial layer. This study aimed to elucidate the elucidation of the link between calcification and atherosclerotic disease in the intracranial vasculature. Methods Consecutive patients with acute ischemic stroke were included. Bilateral intracranial segment of the internal carotid artery, M1 segment of the middle cerebral artery, intracranial segment of the vertebral artery, and the basilar artery were visualized by multi-detector computer tomography (CT) and vessel-wall magnetic resonance imaging (vwMRI) within 14 days after stroke onset. IAC was into intimal or medial pattern. Subsequently, on the vwMRI, we assessed luminal stenosis, eccentricity, plaque burden and intraplaque hemorrhage as markers of atherosclerosis at each IAC site. Results Among 69 stroke patients, IAC was identified in 35% of (161/483) artery segments, of which 61.5% were predominantly intimal calcification and 38.5% were predominantly medial calcification. 79.8% of intimal calcifications and 64.5% of medial calcifications co-existed with atherosclerotic plaques. Intimal calcification was associated with luminal stenosis (p=0.003) caused by atherosclerotic lesions. Compared to medial IAC, intimal IAC was more often accompanied by eccentric plaques (p=0.02), larger plaque burden (p=0.001) and intraplaque hemorrhage (p=0.001). Conclusion Our multimodal imaging-based comparison study on intracranial arteriosclerosis demonstrated that intimal IAC, compared to medial IAC, was more often accompanied by luminal stenosis, larger plaque burden, eccentricity, and intraplaque hemorrhage, providing strong evidence for clinical evaluation on mechanism, risk and prognosis of ischemic stroke.